Waste Heat Recovery for the Cement Sector : Market and Supplier Analysis - International Finance Corporation (World Bank Group, Washington, DC, 2014)
This report analyzes the current status of Waste Heat Recovery (WHR) technology deployment in developing countries and investigates the success factors in countries where WHR has become widely spread. The report then focuses on the in-depth analysis of WHR potential and enabling factors in eleven country markets in Africa (Nigeria, South Africa), South Asia (India, Pakistan), Middle East (Egypt, Turkey), Latin America (Brazil, Mexico) and East Asia (Philippines, Thailand, Vietnam). The report maps out major WHR equipment suppliers. In addition, the report includes a brief analysis of business and project models used internationally to support WHR deployment.